Techno-economic assessment of microalgae cultivation in a tubular photobioreactor for food in a humid continental climate - Schade, S.; Meier, T. (2021)
Fish as the primary source for the essential n − 3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) cannot cover the global demand for these important nutrients resulting in a supply gap of currently 1.1 million tons of EPA + DHA annually. A further exploitation of natural fish stocks is linked to great damage to ecosystems. Oleaginous microalgae are a natural source for EPA and DHA and could possibly contribute to closing this gap. The cultivation in photobioreactors (PBR) in a ‘cold-weather’ climate showed that microalgae compare favorably to aquaculture fish. The present study assesses the economic potential of microalgae for food in such system model. Techno-economic assessment was conducted on the basis of a dynamic system model for the cultivation of Nannochloropsis sp. in industrial scale in Central Germany over a time span of 30 years. The net present value (NPV) and return-on-investment (ROI) were obtained for a number of scenarios in which technic and economic parameters were altered. Taking the size of the PBR considered into account, the cultivation of Nannochloropsis sp. yielded a positive NPV of EUR 4.5 million after 30 years which translates to an annualized ROI of 1.87%. The sensitivity analysis overall resulted in annualized ROIs between 1.12 and 2.47%. Major expenditures comprised the PBR infrastructure, maintenance and labor cost. An extended cultivation season by four weeks was responsible for an NPV surplus of almost one third (32%). An increase in the selling price by 15% was responsible for a 47% higher NPV. In comparison with Atlantic salmon (Salmo salar) raised in aquaculture, EPA from Nannochloropsis sp. resulted in about halved cultivation costs (− 44 to − 60%). In this study we could show that microalgae from photoautotrophic cultivation not only have the potential to supply humans with essential nutrients, but they are also a lucrative investment, even in a ‘cold-weather’ climate where cultivation cannot take place year round. Publikationsfonds MLU